Healthcare professionals’ perceptions about implementing accreditation as a strategy to improve healthcare quality and organisational performance: a cross-sectional survey study - Mohammad J. Alhawajreh; William J. Jackson; Audrey S. Paterson (PLoS ONE, 2025)
Objective This study aims to investigate the healthcare professionals’ perceptions about the impact of accreditation as a strategy to improve the quality of healthcare services and organisational performance in public hospitals in Jordan. Design A cross-sectional survey. Setting Four accredited public hospitals located in three different geographical regions in Jordan. Participants A total of 500 healthcare professionals, including both clinical and non-clinical staff, who worked at the selected hospitals. The data analysis included valid responses from 74.4% of the participants. Methods A web-based questionnaire was applied. To investigate the relationship between the quality results scale (dependent variable) and the other survey scales (independent variables), multiple regression analysis was performed. Results The study showed that the impact of accreditation on the quality of healthcare services was almost high across all scales; the Quality Results and Accreditation Impact scales received the highest mean scores, suggesting that healthcare professionals have a positive perception towards accreditation. Healthcare professionals agree that accreditation has improved the quality of healthcare services and hospitals’ performance in a wide range of clinical and administrative aspects. There was a significant positive correlation between healthcare professionals’ perception of Quality Results (P <  0.001) (dependent variable) and their perception of all other accreditation survey scales (independent variables). Regression analysis showed a significant relationship between Quality Results and Customer or Patient Satisfaction (P <  0.001), Management and Leadership (P =  0.030), and Accreditation Impact (P =  0.001) scales, and these were the most important accreditation predictors of, better quality results. Conclusion The majority of healthcare professionals view accreditation positively, seeing its potential to improve the quality of healthcare and organizational performance. However, there are nuanced variations between administrative and clinical professionals about the aims and objectives of using accreditation as a strategy for healthcare quality improvement. Future research is needed to explore the long-term impact of accreditation and the contextual factors that impact the perceptions of healthcare professionals on accreditation, particularly among different healthcare professional groups. This will help provide policy direction and improve understanding of accreditation’s impact.